Pesawat Tanpa Awak untuk Pemetaan Area Perkebunan - Sugeng Sugeng; Ramadhan Adi Putra; Refinda Fazar Muslim; Yogi Septianto (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2019)
The development of oil palm plantations from the beginning of planting in 1848 until now can be said to be very significant. As the largest palm oil production country in the world Indonesia has many developing palm oil companies, both national and international. To monitor the vast oil palm plantations, a cheaper and more efficient technological innovation is needed. In order to observe the vast plantation area and the different topography of the land, which can complicate logistical access especially if there is rain making access difficult to pass, we conduct research on monitoring and mapping oil palm plantation areas. The monitoring function is to monitor plantation logistics lines such as, finding a faster route by looking at the contour of the land so as to facilitate transportation access from collectors to each existing post. As for mapping, it functions to map an area of ​​225 hectares with the aim of assessing the condition of oil palm plantations, especially assets from the garden itself. this activity is commonly referred to as landholders by surveying assets or inventory. The use of mapping techniques using unmanned aircraft has several advantages, one of which is more accurate mapping than using satellite imagery. From this mapping data can be developed again such as census mapping data, land use maps, land use planning, and monitoring of pests and weeds. The methods we use include improving the quality of camera resolution, adjusting aircraft height, adjusting aircraft speed, making good airframes, using 2 axis gimbals and special image processing methods Keywords : Mapping, Unmanned Aerial Vehicle (UAV), Plantation, Remote Sense, Aerial Photo